A not so happy ending: coital cephalgia resulting from an acute non-traumatic intraparenchymal haemorrhage in a female with no comorbidities. Issue 5 (27th May 2019) - Abdullah, Hafez Mohammad Ammar; Khan, Uzma Ikhtiar; Tariq, Ezza; Omar, Muhammad
Abstract : A sexual headache or coital cephalgia is a headache associated with sexual activity and is a well-recognised condition. It is usually benign, primary and self-limiting. However, occasionally sexual headaches can result from more sinister causes. Intraparenchymal and subdural haemorrhages have been reported as secondary causes of sexual headaches. We present the case of a 61-year-old woman with no comorbidities who presented acutely with a sexual headache and vision loss, and was found to have an occipital and parietal intraparenchymal haemorrhage. She was normotensive and after extensive workup was found to have no predisposing condition for her haemorrhage. The patient had an uneventful recovery with physical rehabilitation and had regular follow-ups, with no residual weakness. She was in a completely normal state of health 1 year after her event, and continued to be off any medications.